JadR*‐mediated feed‐forward regulation of cofactor supply in jadomycin biosynthesis. Issue 4 (17th October 2013) - Zhang, Yanyan; Pan, Guohui; Zou, Zhengzhong; Fan, Keqiang; Yang, Keqian; Tan, Huarong
Summary: Jadomycin production is under complex regulation in Streptomyces venezuelae . Here, another cluster‐situated regulator, JadR*, was shown to negatively regulate jadomycin biosynthesis by binding to four upstream regions of jadY, jadR1, jadI and jadE in jad gene cluster respectively. The transcriptional levels of four target genes of JadR* increased significantly in ΔjadR*, confirming that these genes were directly repressed by JadR*. Jadomycin B (JdB) and its biosynthetic intermediates 2, 3‐dehydro‐UWM6 (DHU), dehydrorabelomycin (DHR) and jadomycin A (JdA) modulated the DNA‐binding activities of JadR* on the jadY promoter, with DHR giving the strongest dissociation effects. Direct interactions between JadR* and these ligands were further demonstrated by surface plasmon resonance, which showed that DHR has the highest affinity for JadR*. However, only DHU and DHR could induce the expression of jadY and jadR * in vivo . JadY is the FMN/FAD reductase supplying cofactors FMNH2 /FADH2 for JadG, an oxygenase, that catalyses the conversion of DHR to JdA. Therefore, our results revealed that JadR* and early pathway intermediates, particularly DHR, regulate cofactor supply by a convincing case of a feed‐forward mechanism. Such delicate regulation of expression of jadY could ensure a timely supply of cofactors FMNH2 /FADH2 for jadomycin biosynthesis, and avoid unnecessary consumption of NAD(P)H.